A V and Fe composite modified molecular sieve and its preparation method and application
The V and Fe composite modified molecular sieve addresses the limitations of existing catalysts by enhancing the production of low-carbon olefins like ethylene and propylene through a novel carbon-carbon bond lattice oxygen activation and homolytic cleavage reaction, improving catalyst efficiency and reducing methane yield.
Patent Information
- Application Number
- CN202311269461.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2043-09-28
AI Technical Summary
Existing metal-modified molecular sieves and their applications in catalytic cracking catalysts are not ideal for increasing the yield of low-carbon olefins like ethylene and propylene, and the use of aluminum sol as a binder limits pore smoothness, hindering the production of these valuable products.
A V and Fe composite modified molecular sieve is prepared by mixing a shape-selective cracking molecular sieve with vanadium and iron compounds, followed by stirring, filtering, washing, drying, and calcining, to enhance the catalyst's performance in producing low-carbon olefins through a carbon-carbon bond lattice oxygen activation and homolytic cleavage reaction mode.
The V and Fe composite modified molecular sieve significantly increases the yield of ethylene and propylene while reducing methane production, demonstrating improved catalyst performance in hydrocarbon catalytic cracking reactions.
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petroleum catalytic cracking catalysts, and specifically relates to a V and Fe composite modified molecular sieve and a preparation method and application thereof. Background Art
[0002] With the rapid development of the petrochemical industry, the demand for ethylene and propylene has continued to grow. In 2013, the domestic demand for propylene was 17.1 million tons / year, and the output was about 14.6 million tons / year, with a large gap between supply and demand. Naphtha steam cracking provides 90% of my country's ethylene and 30% of propylene. Although the steam cracking process is very mature, it has disadvantages such as high construction cost, high energy consumption (reaction temperature greater than 800°C), and high carbon emissions. In order to cope with the increasingly severe global energy consumption and environmental pollution problems, a hydrocarbon catalytic cracking process technology using microsphere catalysts has been developed (Park Yong-Ki, Lee Chul Wee, Kang Na Young, et al. Catalytic cracking of lower-valued hydrocarbons for producing light olefins [J]. Catal Surv Asia, 2010, 14 (2): 75-84). This process converts long-chain hydrocarbons into high-value-added low-carbon olefins such as ethylene and propylene at a higher reaction temperature (600°C-700°C). The cracking reaction pathways of hydrocarbons can be divided into carbon ion mechanism and free radical mechanism. The former mainly produces propylene and butene characteristic products through the action of solid acid, while the latter produces ethylene characteristic products under thermal initiation conditions. In microsphere catalytic cracking catalysts, shape-selective cracking molecular sieves or metal-modified shape-selective cracking molecular sieves are generally used as the main cracking components to achieve the purpose of increasing the production of propylene and ethylene by coordinating carbon ion and free radical reactions.
[0003] However, due to the limitations of modification technology, the existing metal-modified molecular sieves and their application in catalytic cracking catalysts are not ideal. At the same time, the existing catalyst preparation technology mainly uses aluminum sol as the main binder, which is difficult to effectively improve the pore smoothness of the catalyst, thereby limiting the yield of low-carbon olefins in the catalytic cracking process. Summary of the invention
[0004] In view of the problem that metal-modified molecular sieves in the prior art and their application effects in catalytic cracking catalysts are poor, the present invention provides a V and Fe composite modified molecular sieve and its preparation method and application, which can effectively increase the yield of low-carbon olefins such as ethylene and propylene, and show a good effect of reducing methane.
[0005] The present invention is achieved through the following technical solutions:
[0006] A V and Fe composite modified molecular sieve, the preparation method of which is: mixing a shape-selective cracking molecular sieve, a vanadium compound, an iron compound and water into a mixed slurry with a solid content of 10-65%, stirring for 0.1-5h, filtering, washing, drying or directly drying, and then calcining at 300-750°C to obtain the V and Fe composite modified molecular sieve; further preferably, mixing the shape-selective cracking molecular sieve, a vanadium compound, an iron compound and water into a mixed slurry with a solid content of 15-55%, stirring for 0.2-4h, and then filtering, washing, drying, and calcining at 350-700°C to obtain the V and Fe composite modified molecular sieve.
[0007] Furthermore, the shape-selective cracking molecular sieve is one or more of ZSM-5, IM-5, SAPO-34, EU-1, ITQ-13, β zeolite, and MCM-22; the vanadium compound is one or more of vanadium nitrate, vanadium chloride, ammonium metavanadate, and vanadium oxide; and the iron compound is one or more of ferric nitrate, ferric chloride, and ferric oxide.
[0008] Furthermore, the shape-selective cracking molecular sieve is ZSM-5, and the silicon-aluminum molar ratio of ZSM-5 is 15-150, preferably 20-120.
[0009] Furthermore, the weight ratio of the shape selective cracking molecular sieve, the vanadium compound and the iron compound is 1:0.001~0.07:0.01~0.2.
[0010] In the present invention, the preparation method of the V and Fe composite modified molecular sieve is to mix the shape-selective cracking molecular sieve, vanadium compound, iron compound and water into a mixed slurry with a solid content of 10-65%, stir for 0.1-5h, filter, wash, dry or directly dry, and then calcine at 300-750°C to obtain the V and Fe composite modified molecular sieve.
[0011] In the present invention, the V and Fe composite modified molecular sieve is used in the preparation of a catalytic cracking catalyst, wherein the catalytic cracking catalyst comprises the following components in percentage by mass: 5-35% of a phosphorus silicon composite binder, 10-60% of a composite modified molecular sieve, 0-25% of other molecular sieves, 0.2-10% of a metal compound, 0-15% of activated alumina and the balance of natural clay;
[0012] The phosphorus-silicon composite binder includes the following components in parts by weight: 15 to 55 parts of P2O5, 10 to 45 parts of SiO2; the particle size of the phosphorus-silicon composite binder is 5 to 35 nm, and the pH is 0.4 to 4.0; preferably, the phosphorus-silicon composite binder includes the following components in parts by weight: 18 to 50 parts of P2O5, 12 to 42 parts of SiO2; the particle size of the phosphorus-silicon composite binder is 6 to 30 nm, and the pH is 0.6 to 3.5.
[0013] Furthermore, the preparation method of the catalytic cracking catalyst is: uniformly mix the phosphorus-silicon composite binder, V and Fe composite modified molecular sieves, other molecular sieves, metal compounds, activated alumina, natural clay and water to form a slurry with a solid content of 20-60%, and obtain the catalytic cracking catalyst after spray drying and calcination. The preparation method of the phosphorus-silicon composite binder is: mix phosphoric acid and silica sol, and age the mixture at 15°C-95°C for 0.1-5 hours to obtain the phosphorus-silicon composite binder.
[0014] Furthermore, the phosphoric acid is orthophosphoric acid or phosphorous acid; the concentration of the phosphoric acid is 20-62% in terms of P2O5 mass content; the silica sol is 15-50% in terms of SiO2 mass content, has a pH value of 1.0-7.0, contains 20-200 ppm sodium oxide, and has a particle size of 4-35 nm.
[0015] Furthermore, the other molecular sieves are one or more of M-ZSM-5, USY, RE-USY, P-USY, PRE-USY, β zeolite and SAPO-34; the metal compound is one or more of Fe, Ni, Co, Mn, W, Mo, Ce, La, Bi, Cu, Zn, Ti, Cr salts; the activated alumina is one or more of pseudo-boehmite, alumina monohydrate, alumina trihydrate, amorphous alumina; the natural clay is one or more of kaolin, halloysite, montmorillonite, cross-linked layered clay, sepiolite, bentonite, hydrotalcite, diatomaceous earth and rectorite.
[0016] Furthermore, the other molecular sieve is M-ZSM-5, and M-ZSM-5 is one or more of Fe-ZSM-5, Co-ZSM-5, Ni-ZSM-5, Mn-ZSM-5, Ce-ZSM-5, P-ZSM-5, and Fe-P-ZSM-5.
[0017] Furthermore, the spray drying conditions are as follows: an inlet temperature of 300-600°C and an exhaust gas temperature of 100-300°C; the roasting temperature is 300-600°C, and the roasting time is 0.3-3.0h.
[0018] Furthermore, the spray drying conditions are as follows: an inlet temperature of 350-580°C and an exhaust gas temperature of 120-250°C; the roasting temperature is 350-550°C, and the roasting time is 0.5-2.0h.
[0019] Based on the systematic understanding and continuous research on the catalytic cracking reaction mode, the present invention adopts a high-efficiency cracking reaction mode of carbon-carbon bond lattice oxygen activation and homolytic cleavage, which promotes the intermediate cleavage reaction of C5 and C6 alkanes by reducing the activation energy of the cracking reaction, and changes the reaction mode of catalytic thermal cracking, from the end cleavage reaction of the traditional reaction process that produces more methane + ethylene to the homolytic cleavage reaction mode of carbon-carbon bond lattice oxygen activation, which can simultaneously improve the yields of ethylene and propylene and appropriately increase the production of hydrogen.
[0020] Under the guidance of the above-mentioned efficient catalytic cracking reaction mode, the study found that the composite modification of V and Fe improved the L acid (Lewis acid) characteristics of the shape-selective cracking molecular sieve, which can promote the synergistic effect of free radical reaction and positive carbon ion reaction, thereby improving the catalyst's performance in producing more low-carbon olefins. In addition, the existing preparation technology basically uses aluminum sol (~1nm) or phosphorus aluminum inorganic binder as the main binder to ensure the wear resistance of the microsphere catalyst. Due to the small particle size of the aluminum sol, the pores of the catalyst can be blocked to a large extent, limiting the effectiveness of small and medium pore molecular sieves in increasing the production of low-carbon olefins. In view of this, on the basis of the existing technology, the present invention provides a composite modified molecular sieve containing V and Fe and its application in the preparation of catalytic cracking catalysts, which can greatly increase the yield of low-carbon olefins such as ethylene and propylene, and effectively reduce the yield of methane.
[0021] The catalytic cracking catalyst prepared by the V and Fe composite modified molecular sieve of the present invention is used for the catalytic cracking reaction of hydrocarbons (such as naphtha), showing the characteristics of high yield of ethylene and propylene. The catalytic cracking reaction conditions include a reaction temperature of 500°C-750°C, preferably 550°C-700°C, a reaction time of 0.5s-10s, preferably 0.8s-8s, and a catalyst-oil ratio of 3-30, preferably 5-25.
[0022] The beneficial effects achieved by the present invention are:
[0023] The V and Fe composite modified molecular sieve prepared by the present invention can promote the synergistic effect of free radical reaction and positive carbon ion reaction, thereby improving the catalyst's performance in producing more low-carbon olefins. The V and Fe composite modified molecular sieve is applied to the preparation of catalytic cracking catalysts, greatly improving the yield of low-carbon olefins such as ethylene and propylene, and effectively reducing the methane yield. DETAILED DESCRIPTION
[0024] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.
[0025] The analytical test methods used in the embodiments of the present invention are as follows: (1) kaolinite and halloysite: X-ray diffraction method; (2) relative crystallinity and unit cell parameters: X-ray diffraction method; (3) elemental composition and silicon-aluminum ratio: XRF fluorescence method; (4) solid content: ignition method, 800°C / hour; (5) average particle size: laser particle size analyzer method; particle size: TEM electron microscope analysis; (6) specific surface area and pore volume: nitrogen adsorption method; (7) wear index: abrasion meter straight tube method; (8) micro-reaction activity (MA): the raw oil is Dagang light diesel oil, the catalyst loading is 5.0 g, the catalyst-oil ratio is 3.2, the reaction temperature is 460°C, the reaction time is 70 seconds, and MA = (gasoline below 200°C in the product + gas + coke) / total amount of oil input × 100%.
[0026] Specifications of raw materials used in the embodiments of the present invention (all in weight percentage):
[0027] (1) 1# orthophosphoric acid, P2O5 61.5%; 2# orthophosphoric acid, P2O5 30%; 1# silica sol, SiO2 30%, pH 2.8, sodium oxide 120ppm, particle size 12nm; 2# silica sol, SiO2 40%, pH 4.6, sodium oxide 150ppm, particle size 18nm; concentrated hydrochloric acid, 37%, all are industrial products; monoammonium phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), ammonium chloride (NH4Cl), all are chemically pure.
[0028] (2) Ammonium vanadate (NH4VO3), vanadium metanitrate (V(NO3)3), manganese nitrate (Mn(NO3)2.4H2O), manganese chloride (MnCl2), cobalt nitrate (Co(NO3)2.6H2O), cobalt chloride (CoCl2.6H2O), ferric chloride (FeCl3.6H2O), ferric nitrate (Fe(NO3)3.9H2O) are all chemically pure.
[0029] (3) 1# ZSM-5, silicon-aluminum ratio 50, relative crystallinity 93%, sodium oxide 0.07%, solid content 95.0%; 2# ZSM-5, silicon-aluminum ratio 70, relative crystallinity 89%, sodium oxide 0.10, solid content 94.5%; 3# ZSM-5, silicon-aluminum ratio 36, relative crystallinity 91%, sodium oxide 2.65%, solid content 94%; Fe-ZSM-5, Fe2O31.8%, solid content 92.0%; Mn-ZSM-5, MnO2.1%, solid content 94.5%, all are industrial products.
[0030] (4) USY molecular sieve, unit cell parameter 2.427nm, solid content 96.0%; RE-USY, RE2O31.9%, solid content 95.2%, β zeolite, silicon-aluminum ratio 26, solid content 94.4%; SAPO-34, relative crystallinity 88%, solid content 93.2%; β molecular sieve, silicon-aluminum ratio 30, relative crystallinity 85%, solid content 95.9%, all are industrial products.
[0031] (5) Pseudo-boehmite, solid content 61.0%; monohydrate alumina, solid content 71.5%; aluminum sol, Al2O3 23.5%, all are industrial products.
[0032] (6) Kaolin: kaolinite content 87%, solid content 87.5%, average particle size 3.9 μm; halloysite: halloysite content 76%, solid content 85.4%, average particle size 4.1 μm; montmorillonite: solid content 84.6%, average particle size 4.3 μm, all are industrial products.
[0033] Now, the following will be described with reference to specific embodiments and comparative examples:
[0034] Example 1
[0035] Preparation of V and Fe composite modified molecular sieve:
[0036] In 2.3 kg of distilled water, 10 g of ammonium metavanadate and 303 g of ferric nitrate nonahydrate were added, and 2.0 kg of 1# ZSM-5 molecular sieve and 0.6 kg of β molecular sieve were added under stirring. The stirring was continued for 3 hours to obtain a mixed slurry, which was then dried at 120°C for 15 hours. After drying and crushing, the mixture was calcined at 550°C for 3.0 hours to obtain a V and Fe composite modified molecular sieve (FG-1).
[0037] Example 2
[0038] Preparation of V and Fe composite modified molecular sieve:
[0039] In 2.3 kg of distilled water, 65 g of vanadium nitrate and 60 g of ferric chloride hexahydrate were added, and 2.3 kg of 2# ZSM-5 molecular sieve and 0.3 kg of SAPO-34 molecular sieve were added under stirring. The mixture was stirred for 1.5 hours to obtain a mixed slurry, which was then dried at 150°C for 10 hours. After drying and crushing, the mixture was calcined at 600°C for 2.0 hours to obtain a V and Fe composite modified molecular sieve (FG-2).
[0040] Example 3
[0041] Preparation of V and Fe composite modified molecular sieve:
[0042] In 10 kg of distilled water, add 30 g of ammonium metavanadate and 110 g of ferric chloride hexahydrate, add 2.6 kg of 3# ZSM-5 molecular sieve and 200 g of ammonium chloride under stirring, raise the temperature to 75°C, continue stirring at constant temperature for 1 hour to obtain a mixed slurry, then filter, wash with 10 kg of 70°C water, flash dry the filter cake at 200°C, dry and crush, and then calcine at 650°C for 1.0 hour to obtain a V and Fe composite modified molecular sieve (FG-3).
[0043] Comparative Example 1
[0044] Comparison of preparation of modified molecular sieves:
[0045] A comparative modified molecular sieve (DZ-1) was prepared by using 1# ZSM-5 molecular sieve according to the method of Example 1 of patent CN101733140A.
[0046] Comparative Example 2
[0047] Comparison of preparation of modified molecular sieves:
[0048] A comparative modified molecular sieve (DZ-2) was prepared by using 2# ZSM-5 molecular sieve according to the method of Example 3 of patent CN1465527A.
[0049] The physical and chemical properties of the composite modified molecular sieves FG-1, FG-2, FG-3 prepared in Examples 1 to 3 and the comparative modified molecular sieves DZ-1 and DZ-2 prepared in Comparative Examples 1 and 2 were analyzed, and the results are shown in Table 1 below:
[0050] Table 1
[0051] .
[0052] Example 4
[0053] Preparation of phosphorus silicon composite binder:
[0054] 900 g of 1# orthophosphoric acid and 1100 g of 1# silica sol were mixed evenly, and reacted at 80°C for 0.2 hours to obtain 1# phosphorus-silicon composite binder.
[0055] Example 5
[0056] Preparation of phosphorus silicon composite binder:
[0057] 1340g 1# orthophosphoric acid and 660g 1# silica sol were mixed evenly, and reacted at 20°C for 2.0 hours to obtain 2# phosphorus-silicon composite binder.
[0058] Example 6
[0059] Preparation of phosphorus silicon composite binder:
[0060] Mix 1320g 2# orthophosphoric acid and 1000g 2# silica sol evenly, and react at 55°C for 0.5 hour to obtain 3# phosphorus-silicon composite binder.
[0061] The composition of the phosphorus-silicon composite binder prepared in Examples 4 to 6 was analyzed, and the results are shown in Table 2 below:
[0062] Table 2
[0063] .
[0064] Example 7
[0065] Preparation of catalytic cracking catalyst:
[0066] Deionized water, kaolin and FG-1 were mixed and slurried for 60 minutes, and then manganese chloride was added and stirred for 20 minutes. Then 1# phosphorus silicon binder was added and slurried for 30 minutes. After high-speed shear treatment (6000r / min) for 2 hours, a slurry with a solid content of 45% was obtained, which was then spray-dried and formed at an inlet temperature of 560°C and an exhaust gas temperature of 190°C. The microspheres obtained by spray drying were calcined at 550°C for 60 minutes to obtain catalytic cracking catalyst B-1.
[0067] Example 8
[0068] Preparation of catalytic cracking catalyst:
[0069] Deionized water, kaolin, USY and FG-2 were mixed and slurried for 80 minutes, and then cobalt nitrate was added and stirred for 30 minutes. Then 1# phosphorus silicon binder was added and slurried for 40 minutes. After high-speed shear treatment (6000r / min) for 2 hours, a slurry with a solid content of 50% was obtained, which was then spray-dried and formed at an inlet temperature of 540°C and an exhaust gas temperature of 170°C. The microspheres obtained by spray drying were calcined at 600°C for 40 minutes to obtain catalytic cracking catalyst B-2.
[0070] Example 9
[0071] Preparation of catalytic cracking catalyst:
[0072] Deionized water, halloysite, pseudo-boehmite, Fe-ZSM-5 and FG-2 were mixed and slurried for 60 minutes, and then ferric chloride was added and stirred for 20 minutes. Then 2# phosphosilicate binder was added and slurried for 30 minutes. After high-speed shear treatment (6000r / min) for 2 hours, a slurry with a solid content of 40% was obtained, which was then spray-dried and formed at an inlet temperature of 550°C and an exhaust gas temperature of 180°C. The microspheres obtained by spray drying were calcined at 550°C for 60 minutes to obtain catalytic cracking catalyst B-3.
[0073] Example 10
[0074] Preparation of catalytic cracking catalyst:
[0075] Deionized water, montmorillonite, SAPO-34 and FG-2 were mixed and slurried for 80 minutes, and then cobalt chloride and manganese nitrate were added, stirred for 30 minutes, and then 3# phosphorus silicon binder was added, and slurry was beaten for 40 minutes. After high-speed shear treatment (6000r / min) for 2 hours, a slurry with a solid content of 45% was obtained, which was then spray-dried and formed at an inlet temperature of 540°C and an exhaust gas temperature of 170°C. The microspheres obtained by spray drying were calcined at 600°C for 40 minutes to obtain catalytic cracking catalyst B-4.
[0076] Embodiment 11
[0077] Preparation of catalytic cracking catalyst:
[0078] Deionized water, kaolin, alumina monohydrate, REUSY and FG-3 were mixed and slurried for 80 minutes, and then ferric nitrate was added and stirred for 30 minutes. Then 3# phosphorus silicon binder was added and slurried for 40 minutes. After high-speed shear treatment (6000r / min) for 2 hours, a slurry with a solid content of 38% was obtained, which was then spray-dried and formed at an inlet temperature of 560°C and an exhaust gas temperature of 180°C. The microspheres obtained by spray drying were calcined at 600°C for 40 minutes to obtain catalytic cracking catalyst B-5.
[0079] Example 12
[0080] Preparation of catalytic cracking catalyst (the phosphorus silicon composite binder raw material is directly added to the catalyst colloid system, which has the same effect as directly adding 3# phosphorus silicon binder, and the addition ratio of 2# orthophosphoric acid and 2# silica sol is the same as that in Example 6);
[0081] Deionized water, kaolin, 2# orthophosphoric acid, β-zeolite, Fe-ZSM-5 and FG-3 were mixed and slurried for 100 minutes, and then ferric chloride was added and stirred for 30 minutes. Then 2# silica sol was added and slurried for 40 minutes. After high-speed shear treatment (6000r / min) for 2 hours, a slurry with a solid content of 47% was obtained, which was then spray-dried and formed at an inlet temperature of 540°C and an exhaust gas temperature of 170°C. The microspheres obtained by spray drying were calcined at 600°C for 40 minutes to obtain catalytic cracking catalyst B-6.
[0082] Comparative Example 3
[0083] Preparation of comparative catalytic cracking catalyst:
[0084] Referring to Example 7, DZ-1 prepared in Comparative Example 1 was used instead of FG-1, and other raw materials and preparation methods remained unchanged to obtain comparative catalytic cracking catalyst DC-1.
[0085] Comparative Example 4
[0086] Preparation of comparative catalytic cracking catalyst:
[0087] Referring to Example 7, DZ-2 prepared in Comparative Example 2 was used instead of FG-1, and other raw materials and preparation methods remained unchanged to obtain comparative catalytic cracking catalyst DC-2.
[0088] The preparation methods of catalytic cracking catalysts in Examples 7 to 11 and comparative catalytic cracking catalysts in Comparative Examples 3 to 4 are shown in Table 3 below (parts by weight are shown in brackets):
[0089] Table 3
[0090]
[0091] Application Examples
[0092] Embodiment 13
[0093] Taking a fixed fluidized bed reactor as an example, the reaction effects of catalytic cracking catalysts B-1~6 and comparative catalytic cracking catalysts DZ1~2 are explained.
[0094] The catalytic cracking catalyst was treated at 800°C and 100% steam for 10 hours. In a fixed fluidized bed device, the catalytic cracking reaction was carried out with the naphtha shown in Table 4 as the raw material, the reaction temperature was 650°C, the catalyst-oil ratio was 15, and the catalyst loading was 60 grams; the reaction effects of the catalytic cracking catalysts B-1~6 and the comparative catalytic cracking catalysts DZ1~2 are shown in Table 5 below:
[0095] Table 4
[0096]
[0097] Table 5
[0098]
[0099] It can be seen from Table 5 that, compared with the comparative modified molecular sieve catalyst, the catalytic cracking catalyst prepared by using the composite modified molecular sieve of the present invention has significantly increased liquefied gas yield and diene (ethylene + propylene) yield, decreased methane yield, and increased hydrogen yield, showing excellent catalytic cracking reaction performance.
Claims
1. Application of a V and Fe composite modified molecular sieve in the preparation of a catalytic cracking catalyst, characterized in that: The catalytic cracking catalyst comprises the following components in percentage by mass: 5-35% of phosphorus-silicon composite binder, 10-60% of composite modified molecular sieve, 0-25% of other molecular sieves, 0.2-10% of metal compound, 0-15% of activated alumina and the balance of natural clay; The phosphorus-silicon composite binder includes the following components in parts by weight: 15-55 parts of P2O5, 10-45 parts of SiO2; the particle size of the phosphorus-silicon composite binder is 5-35 nm, and the pH is 0.4-4.0; The preparation method of the V and Fe composite modified molecular sieve is as follows: shape-selective cracking molecular sieve, vanadium compound, iron compound and water are mixed into a mixed slurry with a solid content of 10-65%, stirred for 0.1-5 hours, filtered, washed, dried or directly dried, and then calcined at 300-750°C to obtain the V and Fe composite modified molecular sieve.
2. The use of the V and Fe composite modified molecular sieve according to claim 1 in the preparation of a catalytic cracking catalyst, characterized in that: The shape-selective cracking molecular sieve is one or more of ZSM-5, IM-5, SAPO-34, EU-1, ITQ-13, β zeolite, and MCM-22; the vanadium compound is one or more of vanadium nitrate, vanadium chloride, and ammonium metavanadate; and the iron compound is one or more of ferric nitrate and ferric chloride.
3. The use of the V and Fe composite modified molecular sieve according to claim 1 in the preparation of a catalytic cracking catalyst, characterized in that: The shape-selective cracking molecular sieve is ZSM-5, and the silicon-aluminum molar ratio of ZSM-5 is 15-150.
4. The use of the V and Fe composite modified molecular sieve according to claim 1 in the preparation of a catalytic cracking catalyst, characterized in that: The weight ratio of the shape-selective cracking molecular sieve, the vanadium compound and the iron compound is 1:0.001-0.07:0.01-0.
2.
5. The use of the V and Fe composite modified molecular sieve according to claim 1 in the preparation of a catalytic cracking catalyst, characterized in that: The preparation method of the catalytic cracking catalyst is as follows: a phosphorus-silicon composite binder, a V and Fe composite modified molecular sieve, other molecular sieves, a metal compound, activated alumina, natural clay and water are uniformly mixed to form a slurry with a solid content of 20-60%, and the slurry is spray-dried and calcined to obtain a catalytic cracking catalyst; The preparation method of the phosphorus-silicon composite adhesive is as follows: phosphoric acid and silica sol are mixed, and the mixture is aged at 15° C. to 95° C. for 0.1 to 5 hours to obtain the phosphorus-silicon composite adhesive.
6. The use of the V and Fe composite modified molecular sieve according to claim 5 in the preparation of a catalytic cracking catalyst, characterized in that: The phosphoric acid is orthophosphoric acid or phosphorous acid; the concentration of the phosphoric acid is 20-62% in terms of P2O5 mass content; the silica sol has a SiO2 mass content of 15-50%, a pH value of 1.0-7.0, sodium oxide of 20-200 ppm, and a particle size of 4-35 nm.
7. The use of the V and Fe composite modified molecular sieve according to claim 5 in the preparation of a catalytic cracking catalyst, characterized in that: The other molecular sieves are one or more of M-ZSM-5, USY, RE-USY, P-USY, PRE-USY, β zeolite and SAPO-34; the metal compound is one or more of Fe, Ni, Co, Mn, W, Mo, Ce, La, Bi, Cu, Zn, Ti, Cr salts; the activated alumina is one or more of pseudo-boehmite, alumina monohydrate, alumina trihydrate, amorphous alumina; the natural clay is one or more of kaolin, montmorillonite, sepiolite, bentonite, hydrotalcite, diatomaceous earth, rectorite.
8. The use of the V and Fe composite modified molecular sieve according to claim 5 in the preparation of a catalytic cracking catalyst, characterized in that: The spray drying conditions are as follows: an inlet temperature of 300-600°C and an exhaust gas temperature of 100-300°C; the roasting temperature is 300-600°C and the roasting time is 0.3-3.0h.
Citation Information
Patent Citations
Preparation method of shape-selective molecular sieve combination
CN101733140A
